2015
DOI: 10.1210/jc.2015-2263
|View full text |Cite
|
Sign up to set email alerts
|

Severe Early-Onset Obesity Due to Bioinactive Leptin Caused by a p.N103K Mutation in the Leptin Gene

Abstract: Context:Congenital leptin deficiency is a very rare cause of severe early-onset obesity. We recently characterized a mutation in the leptin gene (p.D100Y), which was associated with detectable leptin levels and bioinactivity of the hormone.Case Description:We now describe two siblings, a 9-year-old girl and a 6-year-old boy with severe early-onset obesity and hyperphagia, both homozygous for a c.309C>A substitution in the leptin gene leading to a p.N103K amino acid exchange in the protein and detectable circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 10 publications
3
78
0
15
Order By: Relevance
“…Despite their severe obesity, both children had undetectable levels of serum leptin and a mutation in the gene encoding leptin mapped at 7q32.1. The disease is caused by mutations in the LEP gene (OMIM *164160) typically leading to defects in protein synthesis or secretion, and therefore to the absence or very low blood levels of this hormone [21][22][23].…”
Section: Congenital Leptin Deficiency (Omim #614962)mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite their severe obesity, both children had undetectable levels of serum leptin and a mutation in the gene encoding leptin mapped at 7q32.1. The disease is caused by mutations in the LEP gene (OMIM *164160) typically leading to defects in protein synthesis or secretion, and therefore to the absence or very low blood levels of this hormone [21][22][23].…”
Section: Congenital Leptin Deficiency (Omim #614962)mentioning
confidence: 99%
“…However, recently the first cases of functional leptin deficiency have been described [23,24]. This entity is characterized by detectable immunoreactive levels of circulating leptin, but bioinactivity of the hormone due to defective receptor binding [23,24].…”
Section: Congenital Leptin Deficiency (Omim #614962)mentioning
confidence: 99%
See 1 more Smart Citation
“…The most common form is caused by heterozygous mutations in the melanocortin 4 receptor gene ( MC4R ) . Other causes are, eg, biallelic mutations in the leptin gene ( LEP ), leptin receptor gene ( LEPR ), or proopiomelanocortin gene ( POMC ) …”
Section: Introductionmentioning
confidence: 99%
“…It is located on chromosome 7q31.3 in humans and consists of three exons spanning 650 kb [9]. Mutations of the LEP gene have been associated with different degrees of obesity in the human population [10,11]. Moreover, in obese families, recent studies have shown an association of different single nucleotide polymorphisms (SNPs) in the LEP gene with serum leptin levels, obesity and metabolic biomarkers, including anthropometric parameters, levels of glucose, insulin and lipid profile [12,13].…”
Section: Introductionmentioning
confidence: 99%